Modification of Teaching Behaviour through Micro Teaching - Ahmad, DR. Sarfaraz; Sultana, DR. Afroz (INDIAN EDUCATIONAL REVIEW, 2013)
Teacher education programme in India requires too much of improvement. Micro-teaching comes as remedy to the difficulties of teacher education programme. Present study aimed to study the modification of teaching behaviour of pupil teachers through micro-teaching approach. The sample consisted of 60 pupil teachers at teachers training colleges of Gorakhpur University. The testing of hypothesis is done by comparing the scores of the two group using the “t” test. Result indicated there is remarkable change in teaching behaviours of teachers through micro-teaching programme.